Between eroticism and social criticism; The literariness of Shahnon Ahmad's "Terdedah" (1965) - Abdul Rani, Mohd Zariat (Wacana, Journal of the Humanities of Indonesia, 2009)
In the history of modern Malay literature, the 1960s are labelled by many literary critics as era picisan (the age of dime fiction) because of the flood of karya picisan (dime fiction) in the local market. Karya picisan here refers to works that clearly manipulate sexual themes, with the intent of conjuring an atmosphere of eroticism to attract readers. Critics generally do not consider these works to be karya sastra (literary works) because they do not fulfil two important criteria that commonly classify the term 'literature', namely bahasa yang indah (aesthetic language) and isi yang berfaedah (beneficial content). In the context of this definition of 'literature', Shahnon Ahmad's 1965 novel Terdedah is considered problematic because of incongruities in the estimation of its 'literariness'. As opposed to critics who initially labelled it karya picisan, the 'literariness' of Terdedah was defended by its own author because it contained elements social criticism. This difference in opinion raises an important point regarding the commonly accepted definitions of 'literature' and 'literariness' in Malay literature: after Shahnon proclaimed his novel's worth based on its social criticism, critical reception towards Terdedah showed an unmistakable shift. With respect to this shift of opinion, this article will perform a critical analysis of the meaning of 'literariness' in relation to Terdedah, and in doing so, clearly determine its status as either a karya picisan or karya sastra, based on the definition of 'literature' practised in Malay literature.